A Score of Low-Grade Inflammation for Predicting Stroke Recurrence in Patients with Ischemic Stroke - Wu M (Dove Medical Press, 2021)
Min Wu,1,* Xiaohao Zhang,2,* Jingjing Chen,3,* Mingming Zha,4 Kang Yuan,5 Kangmo Huang,2 Yi Xie,2 Jianzhong Xue,6 Xinfeng Liu1,2,7 1Department of Neurology, Jinling Hospital, The First School of Clinical Medicine, Southern Medical University, Nanjing, 210002, People’s Republic of China; 2Department of Neurology, Jinling Hospital, Affiliated Medical School of Nanjing University, Nanjing, 210002, People’s Republic of China; 3Department of Neurology, Changhai Hospital, Navy Medical University, Shanghai, 200433, People’s Republic of China; 4Department of Neurology, Jinling Hospital, Medical School of Southeast University, Nanjing, 210002, People’s Republic of China; 5Department of Neurology, Jinling Hospital, Nanjing Medical University, Nanjing, 210000, People’s Republic of China; 6Department of Neurology, Changshu No.2 People’s Hospital, Changshu, People’s Republic of China; 7Stroke Center & Department of Neurology, the First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui, 230001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xinfeng LiuDepartment of Neurology, Jinling Hospital, The First School of Clinical Medicine, Southern Medical University, No. 305 Zhongshan East Road, Xuanwu District, Nanjing, Jiangsu Province, 210002, People’s Republic of ChinaTel +86 138 13835114Email xfliu2@vip.163.comJianzhong XueDepartment of Neurology, Changshu No.2 People’s Hospital, No. 18 Taishan Road, Changshu, Jiangsu Province, People’s Republic of ChinaTel +86 13506247572Email xjz2021@sina.comBackground and Purpose: The impact of low-grade inflammation (LGI) on stroke recurrence has not been well studied yet. We aimed to evaluate the association between LGI and stroke recurrence in patients with ischemic stroke.Methods: Patients with first-ever ischemic stroke diagnosed within 72 hours of symptoms onset were consecutively recruited from the Nanjing Stroke Registry Program. C-reactive protein (CRP) level, white blood cell (WBC) count, platelet (PLT) count, and neutrophil-to-lymphocyte ratio (NLR) were conceived as low-grade inflammation biomarkers and combined into a standardized LGI score. The association of LGI score with the risk of stroke recurrence was analyzed with multivariate Cox regression models. Analyses accounting for the competing risk of stroke recurrence and death were also performed.Results: Of the 1214 patients studied (median age, 61 years; male, 71.6%), 177 (14.6%) patients experienced a recurrent stroke with a median follow-up of 23.0 (interquartile ranges, 14.5– 34.0) months. Patients with stroke recurrence had a higher LGI score (median, 3 versus − 2; P < 0.001) than those without recurrence. The univariate analysis indicated that patients with LGI scores in the fourth quartile were more likely to have a stroke recurrence (hazard ratios [HR], 4.312; 95% confidence interval [CI], 2.675– 6.952; P < 0.001). After adjusting for potential confounders, the association remained significant in the multivariate Cox regression model (HR, 4.080; 95% CI, 2.420– 6.879; P < 0.001). Competing risks model and sensitivity analysis further confirmed this conclusion.Conclusion: This study showed that an elevated LGI score was associated with a higher risk of stroke recurrence, independent of other vascular risk factors.Keywords: low-grade inflammation, stroke recurrence, ischemic stroke, predictor